The Impact of Smartphone Use on Students' Motor Skills and Emotional Well-being: A Comprehensive Study - Methodius Tigor; Agata Putri Handayani Simbolon (Jurnal Ilmu Pendidikan dan Humaniora, 2023)
The widespread adoption of smartphones among students has raised intriguing questions about their potential influence on various aspects of development, including motor skills and emotional well-being. This research undertook a comprehensive investigation into these relationships, employing a mixed-methods approach encompassing surveys, interviews, and observational assessments. The findings revealed a complex interplay between smartphone use and motor skills. While certain aspects of motor development exhibited negative associations with prolonged smartphone usage, nuances emerged when considering the types of activities engaged in and the presence of parental guidance. These results underscore the significance of maintaining a balanced approach to technology use that encourages physical activity alongside screen time. In the realm of emotional well-being, this study unveiled a spectrum of effects associated with smartphone use. While some students reported experiencing stress, anxiety, and social comparison related to their digital interactions, others discovered solace in mindfulness apps and maintained positive social connections. These results underscore the need for comprehensive digital literacy programs to empower students with the skills to navigate the emotional landscape of the digital age adeptly. Furthermore, the research highlights the pivotal roles of parents and educators in guiding responsible smartphone use. Parents are instrumental in setting boundaries, fostering healthy technology habits, and promoting a harmonious equilibrium between virtual and real-world experiences. Educators, on the other hand, can harness the potential of smartphones for educational enrichment, leveraging interactive learning and digital resources to enhance students' academic journeys. In conclusion, this research elucidates the intricate relationship between smartphone use and students' motor skills and emotional well-being. Recognizing the dual nature of technology's impact, it emphasizes the importance of conscientious engagement with smartphones to maximize their advantages while mitigating potential risks. As we navigate the digital era, the insights from this study contribute to informed discussions, enabling educators, parents, and policymakers to craft strategies that harness the potential of smartphones as tools for empowerment and enrichment in the lives of students.